Composite Scattering from a PEC Object above Two-Layered Rough Soil Surfaces Based on an Efficient Bi-Iterative Model - Ke Li; Lixin Guo; Juan Li (International Journal of Antennas and Propagation, 2022)
In the study, an efficient bi-iterative physical optics (PO) electromagnetic model is used to analyze the composite scattering from a PEC object above two-layered rough soil surfaces for the first time. The PO method is applied to calculate the direct scattered fields from the object and the upper layer rough surface and to deal with the mutual coupling effect between the object and the two-layered rough surfaces. During the mutual coupling process, a bi-iterative strategy is considered to solve the coupling interaction between the object and the upper rough surface and the coupling interaction between the upper and lower rough surfaces. We assume a 2-D scattering problem. The result is validated by comparing it with that obtained from the conventional method of moments (MoM). Comparison results from different object types show that the scattered curves calculated using the proposed method resemble the ones obtained from MoM. The comparison of computer resources also shows the efficiency of our method. Meanwhile, the normalized radar cross-section of the composite model is analyzed under different parameters.